The World Hip Trauma Evaluation sStudy 3: hemiarthroplasty evaluation by multicentre investigation - WHITE 3: HEMI - an abridged protocol - Sims, A; Parsons, N; Achten, J; Griffin, X; Costa, M; Reed, M (British Editorial Society of Bone and Joint Surgery, 2016)
Approximately half of all hip fractures are displaced intracapsular fractures. The standard treatment for these fractures is either hemiarthroplasty or total hip arthroplasty. The recent National Institute for Health and Care Excellence (NICE) guidance on hip fracture management recommends the use of 'proven' cemented stem arthroplasty with an Orthopaedic Device Evaluation Panel (ODEP) rating of at least 3B (97% survival at three years). The Thompsons prosthesis is currently lacking an ODEP rating despite over 50 years of clinical use, likely due to the paucity of implant survival data. Nationally, adherence to these guidelines is varied as there is debate as to which prosthesis optimises patient outcomes.This study design is a multi-centre, multi-surgeon, parallel, two arm, standard-of-care pragmatic randomised controlled trial. It will be embedded within the WHiTE Comprehensive Cohort Study (ISRCTN63982700). The main analysis is a two-way equivalence comparison between Hemi-Thompson and Hemi-Exeter polished taper with Unitrax head. Secondary outcomes will include radiological leg length discrepancy measured as per Bidwai and Willett, mortality, re-operation rate and indication for re-operation, length of index hospital stay and revision at four months. This study will be supplemented by the NHFD (National Hip Fracture Database) dataset.Evidence on the optimum choice of prosthesis for hemiarthroplasty of the hip is lacking. National guidance is currently based on expert opinion rather than empirical evidence. The incidence of hip fracture is likely to continue to increase and providing high quality evidence on the optimumCite this article: A. L. Sims. The World Hip Trauma Evaluation Study 3: Hemiarthroplasty Evaluation by Multicentre Investigation - WHITE 3: HEMI - An Abridged Protocol. Bone Joint Res 2016;5:18-25. doi: 10.1302/2046-3758.51.2000473.